Reviewing interfirm relationship quality from a supply chain management perspective - Chen Qian; Stefan Seuring; Ralf Wagner (Management Review Quarterly, 2020)
With the overlap of the interfirm relationship quality and supply chain management research in mind, this paper reviewed 100 recent, scientific, English-language papers on interfirm relationship quality based on a categorisation schema derived from a conceptual framework of supply chain management. We aim to contribute to the existing supply chain management literature by providing an insight into the connections of supply chain performance with buyer–supplier relationship quality from the relationship quality scholars' perspective. Through content analysis, frequency and contingency analysis, we evaluated how the three relationship quality dimensions—information, operational, and relational dimensions—and the three types of supply chain performance—financial and market, operational, and relational performance have been reflected in the current interfirm relationship quality papers and how the scholars have tended to link them to each other. The results reveal that relational dimension plays a key role in SC relationship management and influences performance significantly. Information dimension will affect performance indirectly through relational dimension. However, the impact of the operational dimension on performance varies. In addition, buyers' and suppliers' perspectives on the relational drivers of their financial performance may differ. Based on the findings, we suggest promising avenues for future investigation of supply chain relationship and performance.
Keywords: 650; Relationship quality; Supply chain management; Supply chain performance; Buyer–supplier relationship; Literature review; M110; M310